(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
Cholesterol is one of the important components of biological membranes. It is associated with milk fat in milk and milk products. Cholesterol present in animal origin foods undergoes autoxidation during processing as well as during storage yielding toxic products commonly known as cholesterol oxidation products (COPs). The COPs are significantly affected the human health such as atherosclerosis, inflammation, cancer, neurodegenerative diseases etc. Various methods are reported in literature for determination of cholesterol and its oxidation products in milk and milk products.